2007
DOI: 10.1143/jjap.46.2727
|View full text |Cite
|
Sign up to set email alerts
|

Top Emission Organic Light-Emitting Diodes with Double-Metal-Layer Anode

Abstract: Total charge transfer cross sections for Be4++H( 1s) collisions have been calculated for Be4+ impact energies E = 0.1-25.0 keV amu-' using a molecular orbital closecoupling method. Calculated results are compared with other theoretical results and with the experimental data for C4+ + H( 1s) collisions.Recently, various theoretical approaches for charge transfer collisions between light bare ions and atomic hydrogen have appeared (Bransden and Janev 1983). At low impact energies where the impact velocities are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2008
2008
2010
2010

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…22) Tsai et al reported on a study of Al/AuGeNi multilayer anodes for improving luminescence efficiency. 23) In this study, we report on a triple-metal-layer anode with Al/Ni/Au for TEOLEDs, where Al has high reflectivity and Ni/Au has high work function for high holeinjection. The LiF/Al/Ag multilayer was employed as the cathode because it is both optically transmissive and effective as an electron-injection contact.…”
Section: Introductionmentioning
confidence: 99%
“…22) Tsai et al reported on a study of Al/AuGeNi multilayer anodes for improving luminescence efficiency. 23) In this study, we report on a triple-metal-layer anode with Al/Ni/Au for TEOLEDs, where Al has high reflectivity and Ni/Au has high work function for high holeinjection. The LiF/Al/Ag multilayer was employed as the cathode because it is both optically transmissive and effective as an electron-injection contact.…”
Section: Introductionmentioning
confidence: 99%
“…However, Cu substrate surface is not entirely flat and often with raised points. Under high voltage or high current density of devices operation, a great amount of electric currents are concentrated on the raised points, causing devices breakdown or short circuit and generating joule heat, reducing emission performance and shortened life of devices [4]. In this experiment, LED glue is rotated and applied onto the Cu substrate to effectively flatten the surface as the isolation layer to explore the influences of thermal Cu substrate on devices radiation.…”
Section: Introductionmentioning
confidence: 99%